Machina Ex Machina Artificially Intelligent Systems as Inventors under Polish Legal Framework - Bar, Aleksandra (Wroclaw review of law, administration & economics, 2021)
Not only do advanced artificially intelligent (AI) systems play an increasingly important role in modern society, but they also significantly enhance industrial and economic development. AI systems are already capable of generating outputs, which, had they been created by humans, would be eligible for patent protection. Polish patent regime has yet to determine how it will address inventive computational results. This paper aims at addressing a question whether AI-generated outputs can be considered patentable inventions under Polish legal framework and if so, who would be recognized as the inventor. The author draws conclusions de lege lata and briefly outlines de lege ferenda observations. The author argues that vesting the inventor status in one of the persons who contributed to the AI-generated result offers a reasonable incentive to actors involved in the innovation process and, at the same time, leaving aside vexed problem of computational personhood, does not undermine established legal paradigms, in particular the traditional notion of human creator (inventor).